Prinsip-prinsip Bimbingan dan konseling - Titi Sunarti; Safriyah Safriyah; Alya Citra Wulandari; Cika Nuralifa (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2026)
The success of Guidance and Counseling services relies heavily on adherence to fundamental principles such as confidentiality and voluntariness, yet field implementation faces complex challenges regarding educational levels and modern developments. This study aims to analyze the implementation of fundamental guidance and counseling principles and their relevance to religious value integration and technology adaptation. The method used is qualitative with a library research design, analyzing 20 scientific journal articles published between 2020 and 2025. The results show that the implementation of principles is dynamic. At the elementary level, the expertise principle is hindered by classroom teachers doubling roles, while secondary levels face service management challenges. Current relevance is realized through adapting the principle of currentness with web-based technology and the principle of normativeness through Islamic approaches. This study implies the need for strengthening counselor digital competence and providing professional personnel at the elementary level to ensure service integrity.